REHABILITATION OF THE CONSEQUENCES OF PERINATAL PATHOLOGY IN CHILDREN IN THE FIRST YEAR OF LIFE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Perinatal brain damage has been the focus of attention of scientific researchers and practitioners for many years. This continued interest can be explained by the frequency of pathology, high mortality in the neonatal period, as well as subsequent disability from childhood. The frequency of recorded cases of neurological changes in children of the first years of life has increased. Their share today is 27-60% and does not yet have a downward trend. The list of psychoneurological disorders associated with hypoxic brain damage is extremely wide: from delayed psychomotor development to severe forms of cerebral palsy, accompanied by mental disability, movement disorders, and seizures.